State-formation first: Recommendations for reconstruction and peace-making in Afghanistan - Andreas Wimmer; Conrad Schetter (University of Bonn, Center for Development Research (ZEF), 2002)
The Petersberg conference held near Bonn at the beginning of December 2001 and the donor conference held in Tokyo in mid-January 2002 defined the broad outlines for peace-making and reconstruction in Afghanistan. Under the Bonn agreement, a loya jirga consisting of representatives from all the country's regions will agree on a new constitution in the coming months. A new government to replace the transitional government will be chosen in democratic elections to be held in summer 2004. Provided this process of political peace-making and democratisation takes place as planned, the international community intends to provide the financial means to enable this famine-stricken and war-torn country to take a leap forward in development over the next four years. In this paper, the authors suggest a revision of the overall strategy that has been defined and developed up to now... – – Auf der Petersberger Konferenz Anfang Dezember 2001 bei Bonn und der Geberkonferenz in Tokio Mitte Januar 2002 wurden die groben Linien für die Befriedung und den Wiederaufbau Afghanistans definiert. Gemäß des Bonner Abkommens soll eine loya jirga, die sich aus Repräsentanten aller Regionen des Landes zusammensetzt, in den kommenden Monaten eine neue Verfassung verabschieden. Aus demokratischen Wahlen, die im Sommer 2004 stattfinden werden, soll eine neue Regierung hervorgehen, welche die Übergangsregierung abzulösen hat. Vorausgesetzt, dass dieser Prozess der politischen Befriedung und Demokratisierung wie geplant vonstatten geht, will die internationale Gemeinschaft die finanziellen Mittel bereitstellen, um während der nächsten vier Jahre dem ausgehungerten und kriegszerrissenen Land einen Entwicklungssprung nach vorne zu ermöglichen. In diesem Papier befürworten die Autoren eine Revision der Gesamtstrategie, wie sie bisher definiert und ausgearbeitet wurde
Keywords: 300; Political Economy